Employment of crumb rubber tyre in concrete masonry bricks. (2020) - Thakur, Ankush; Senthil, K.; Sharma, Rachit; Singh, A.P.
Abstract: Recently in India, there is an exponential growth in automobile sector leading to increasing demands of tires which further results in huge tire waste after their service life. In light of utilization of this waste tires in construction industry, the investigation mainly focused on the use of waste crumb rubber as a partial replacement of fine aggregates in the production of lightweight masonry bricks. Also, in order to support the sustainable environment, an attempt has been made to utilize tire waste in the form of crumb rubber for the production of bricks. In this study, waste crumb rubber tires were used in partial replacement of fine aggregates for developing bricks. The bricks were developed with varying percentages of crumb rubber i.e. 5%, 10%, 15%, 20% by volume of fine aggregates maintaining water/cement ratio as 0.43 for all chosen mixes. The influence of crumb rubber was studied on both fresh mixes as well as hardened bricks. The fresh properties such as slump and density were studied and quantified the flow ability. The mechanical properties as compressive strength, tensile strength and impact resistance of hardened concrete bricks were studied and regression analysis was carried out to estimate the tensile strength. It is observed that the slump and water absorption increased linearly with increase in percentage of crumb rubber. Upto 10% of crumb rubber, initial rate of water absorption was found increased thereafter it is found to be decreased with increase of crumb rubber. It was also observed that compressive and tensile strength showed linear decrement with increase in percentage of crumb rubber. It was observed that the energy absorption increased by 3.66 times for CR20 mix as compared to CM. It was also observed that the empirical relation helps in predicting the tensile strength and found matching well.